2023
DOI: 10.3390/foods12020236
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Visual Method for Nucleic Acid Detection of Escherichia coli O157:H7 Based on CRISPR/Cas12a-PMNT

Abstract: Rapid, accurate and visual point-of-care testing (POCT) methods for pathogenic bacteria detection are essential for avoiding foodborne diseases caused by pathogens or their toxins. In this study, we proposed a rapid and visual detection method that we named “Cas12aVIP”. By combining recombinase polymerase amplification (RPA), a CRISPR/Cas12a system and a cationic-conjugated polythiophene derivative (poly[3-(3′-N,N,N-triethylamino-1′-propyloxy)-4-methyl-2,5-thiophene hydrochloride] (PMNT) mixed with single-stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recently, a CRISPR/Cas12a‐assisted colorimetric method based on CPs was developed for the detection of pathogens. [ 89 ] Pathogenic bacterial dsDNA was amplified by the recombinase polymerase amplification (RPA) reaction, and then DNA was cleaved via reaction with Cas12a. Finally, PMNT was added to the reaction solution and mixed with lysed DNA.…”
Section: Biological Detectionmentioning
confidence: 99%
“…Recently, a CRISPR/Cas12a‐assisted colorimetric method based on CPs was developed for the detection of pathogens. [ 89 ] Pathogenic bacterial dsDNA was amplified by the recombinase polymerase amplification (RPA) reaction, and then DNA was cleaved via reaction with Cas12a. Finally, PMNT was added to the reaction solution and mixed with lysed DNA.…”
Section: Biological Detectionmentioning
confidence: 99%
“…They finally reported that the Cas12aVIP method produced high specificity and did not interfere with other non-target bacteria. This method ensures that the detection was performed within 40 min and that the signal can be observed with the naked eye under natural light, which presents great potential for multiple applications of rapid detection of nucleic acids without the need for technical expertise or auxiliary equipment [90].…”
Section: ε-Viniferinmentioning
confidence: 99%